Assessing patient satisfaction with practitioner communication: patient-centered care, hospital environment and patient trust in the public hospitals - Arif Jameel; Noman Sahito; Noman Sahito; Wenjing Guo; Sania Khan (Frontiers in Medicine)
IntroductionPatient satisfaction is increasingly an important concern in worldwide health policy. The purpose of this research is to identify the effect of practitioner-patient communication (PPC) and cleanliness on patient satisfaction (PS), as well as the mediating role of patient trust (PT).MethodsData were obtained from 497 patients in public hospitals in Saudi Arabia. The data were analyzed using AMOS 25 and Structural equation modeling (SEM) techniques.ResultsThe results show that practitioner-patient communication and cleanliness positively impact patient satisfaction. Further, it reveals that patient trust mediates practitioner-patient communication, cleanliness, and patient satisfaction.ConclusionThe findings may benefit research and healthcare policy formulators since they examined the patients’ perspective of practitioner-patient communication, cleanliness, and satisfaction at Outpatient Departments of public hospitals. The study offers important insights for healthcare authorities to devise strategies to improve service delivery in public hospitals and ensure patient satisfaction.